An Integrative Islamic Education Organizing Model with Tanzhim Values - Susanda Febriani; Chisebe Syvester; Hamdi Abdul Karim; Muhammad Izharul Haq (At-Ta'lim : Media Informasi Pendidikan Islam, 2024)
ENGLISH: An Integrative Islamic Education Organizing Model with Tanzhim ValuesObjective: This study aims to analyze the organizational model of Islamic education integrated with Tanzhim values in several Islamic educational institutions in Bukittinggi City. This research was conducted at MTsN 1 Bukittinggi, MIS Al Ikhwan, MIN Bukittinggi City, and MAN 1 Bukittinggi in 2024. Methods: The research used a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation. Content analysis was used to interpret and summarize the findings. Results: In response to the challenges of modern society, several redesign steps were identified as potential solutions. These include reassessing the philosophical foundation of educational institutions, integrating Islamic values into the learning process, and implementing the results of the redesign. Conclusion: Integrative Islamic schools play a key role in building students' character based on Tanzhim values. Contribution: This research provides practical guidance for Islamic educational institutions in implementing a more effective organizing system based on Tanzhim values. This model can improve both the reputation and effectiveness of Islamic educational institutions in producing superior generation.INDONESIAN: Model Pengorganisasian Pendidikan Islam Integratif dengan Nilai-Nilai TanzhimTujuan: Tujuan penelitian ini untuk menganalisis model pengoganisasian pendidikan Islam terintegrasi dengan nilai-nilai Tanzhim di several Islamic education institutions in Bukittinggi City. Penelitian ini dilaksanakan di MTsN 1 Bukittinggi, MIS Al Ikhwan, MIN Kota Bukittinggi, and MAN 1 Bukittinggi pada tahun 2024. Metode: Jenis penelitian menggunakan metode kualitatif dengan pendekatan studi kasus. Pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Analisis konten digunakan dalam proses interpretasi dan menyimpulkan data. Hasil: Dalam upaya mengatasi perubahan masyarakat modern, beberapa langkah redesain yang diharapkan dapat menjadi solusi permasalahan ini meliputi pengkajian ulang landasan filosofis lembaga pendidikan, pengintegrasian nilai-nilai Islam ke dalam proses pembelajaran, serta metode implementasi hasil redesain tersebut. Kesimpulan: Sekolah, lembaga pendidikan Islam yang integratif adalah kunci untuk membangun karakter siswa berbasis nilai-nilai Tanzhim. Kontribusi: Penelitian ini memberikan panduan praktis bagi lembaga pendidikan Islam dalam mengimplementasikan sistem pengorganisasian yang lebih baik, berbasis nilai-nilai Tanzhim. Hal ini dapat meningkatkan citra dan efektivitas lembaga pendidikan Islam dalam mencetak generasi yang unggul.